Study of Techniques of Cold Recycling: Second Part (Stages of a cold Recycling Project UIT Emulsion) - Thenoux, Guillermo; García, Gabriel (Revista Ingeniería de Construcción, 2000)
A project of recycling must consider a great number of elements to be analysed in depth, in order to diminish the conditions of uncertainty that typically will be involved in this type of projects and avoid the reduction of the comparatives advantages respect to other rehabilitation alternatives. The present work corresponds to the second publication of three about cold recycling. In the first publication (RIC Issue N° 20 – Vol 14 Nº2) the basic foundations of cold recycling were presented. In this publication, appear the component stages of a cold recycling project and the most important aspects that must be considered in each one of them. This publication is fundamentally oriented to cold in-place recycling with emulsions. However, the most part can also be applied to other types of cold recycling, like recycling with cut-back asphalts or foamed asphalts